Comprehensive knowledge of HIV and STI and its association with contraceptive use among unmarried adolescents: a two-wave longitudinal study in India - Maurya, Chanda; Muhammad, T.; Kundu, Jhumki; Sulaiman, K. M. (Journal of public health, 2025)
Aim Sexual activity among adolescents has shown an increasing trend globally, and with that, developing countries have faced the challenge of addressing the associated risk factors due to a lack of awareness and access to medical facilities. We assessed the comprehensive knowledge of HIV and sexually transmitted infections (STIs) and its association with contraceptive use among Indian adolescents. Subject and methods Data come from the UDAYA (Understanding the lives of adolescents and young adults) longitudinal survey carried out in 2015–2016 (wave 1) and 2018–2019 (wave 2) in two Indian states, Bihar and Uttar Pradesh, with a sample of 7138 unmarried adolescents aged 15–23 years. Random-effects regression analysis was conducted to examine the association of changes in contraceptive use among unmarried adolescents with the comprehensive knowledge of HIV and STIs and other individual- and household-level factors. Results There was a significant increase in the knowledge regarding HIV among the study participants between wave 1 and wave 2 (38.54% vs 50.14%). The increase was minimal in the case of knowledge regarding STIs (18.41% vs 18.97%). Those who had knowledge regarding HIV were more likely (β: 0.010, p < 0.001) to use contraceptives than those who had no knowledge regarding HIV. Similarly, unmarried adolescents who had knowledge regarding STIs were more likely to use contraceptives than their respective counterparts (β: 0.014, p < 0.001). Conclusion Comprehensive knowledge regarding HIV and STIs plays a key role in contraceptive use among unmarried adolescents in India. The findings suggest that awareness about HIV/AIDS may encourage the adolescents and young adults to use contraception to ensure safe sex.